The Effect of Work Ethics on the Teacher's Performance of State Madrasah Ibtidaiyah in Medan City - Rizki Utami Batubara; Darwin Darwin; Yuniarto Mudjisusatyo (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to determine the effect of work ethic on teacher performance. This type of research uses quantitative research with a path analysis approach with a population of 281 State MI teachers in Medan City. Sampling was carried out by Proportional Random Sampling with a total sample of 164 and data collection was carried out using a questionnaire. The questionnaire used was first tested to obtain a valid and reliable instrument. Prior to testing the instrument, a requirements analysis test was carried out as a path analysis requirement, namely the normality test and linearity test. The results of the research findings are that there is a positive direct effect between work ethic on teacher performance.